Tissue adhesive as well as preparation method and application thereof
The protein-replenished sugar tissue adhesive prepared by one-pot cooking method solves the problems of single function, high toxicity and weak adhesion properties of tissue adhesives in the prior art, and achieves efficient adhesive and conductive properties, and is suitable for emergency hemostasis and spinal cord injury repair.
Patent Information
- Application Number
- CN202311248749.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-26
AI Technical Summary
The existing clinical tissue adhesive has a single function, complex preparation, certain toxicity, weak adhesion performance, and no conductive properties, which limits its application in fields such as emergency hemostasis and incompressible nerve hemostasis.
Through a one-pot cooking method, polyphenol functionalized biological proteins, reduced sugars and metal chloride salts were subjected to Maillard chemical reaction and ion complexation reaction to prepare a protein-reduced sugar tissue adhesive with a polymer network structure, and dense and ordered hydrogen bonds were reconstructed by low-temperature incubation to improve their adhesion and conductivity.
A rapidly prepared tissue adhesive is achieved, with excellent adhesive properties, conductivity and biocompatibility, and can be used in the fields of emergency hemostasis, incompressible nerve hemostasis and spinal cord injury repair and regenerative medicine.
Smart Images

Figure CN119701067A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a tissue adhesive and a preparation method and application thereof. Background Art
[0002] Tissue adhesives are a new generation of medical materials that replace medical sutures and staplers. They are considered to be an ideal biomedical material for wound management and wound healing because of their ease of operation and their ability to seal wounds and prevent leakage of body fluids, provide mechanical support, hemostasis, and match the microenvironment of the injured area.
[0003] However, the existing clinical tissue adhesives have the disadvantages of being few in type, having certain toxicity, being complex and slow to prepare, having weak adhesion properties and being non-functional. For example, the fibrin glue commonly used in clinical practice has low adhesion properties and potential immunogenicity; albumin is generally polymerized and cross-linked using toxic aldehyde cross-linking agents (such as glutaraldehyde); cyanoacrylate glue polymerizes quickly but has significantly reduced wet surface adhesion strength and in vivo degradation toxicity, which limits its further application. Although some new adhesive hydrogels formed in some ways have partially solved the toxicity problem, their weak wet surface adhesion strength, poor hemostatic properties and complex preparation procedures have greatly limited their synthesis efficiency and application range. For example, the polymer-based hydrogel adhesives in Chinese invention patents CN113209358A and CN113512133A have complex preparation processes, weak wet surface adhesion, and poor stability of the hydrogel adhesives themselves, resulting in weak mechanical properties of the hydrogel adhesives, which also limits the application of these polymer hydrogel adhesives in emergency hemostasis and incompressible injuries that require high intrinsic sealing strength of the adhesive (such as arterial bleeding, major tissue defect bleeding, nerve bleeding, etc.). In addition, existing tissue adhesives have a single function, and are simply used as dressings or hemostatic agents, and generally do not have conductive properties.
[0004] Based on the technical problems existing in the above-mentioned prior art, the present invention provides a tissue adhesive prepared by a one-pot cooking method with simple heating, which can be quickly prepared within minutes, has adjustable mechanical properties and adhesion properties, and also has rapid hemostatic properties. It also has the characteristics of forming a reversible microbattery and thus having good conductive properties, and can thus be used in the fields of emergency hemostasis of injuries and regenerative medicine. Summary of the invention
[0005] In view of this, in order to solve the above problems, the present invention provides a tissue adhesive and a preparation method and application thereof, aiming to solve the problem that the tissue adhesive prepared by the prior art has a single function and is simply used as a dressing or hemostatic agent and generally has no conductive properties.
[0006] In order to achieve the above-mentioned purpose, the present invention provides a method comprising providing a functionalized protein; modifying or blending the protein with a polyphenol unit-containing substance or a phenolic hydroxyl-containing small molecule to obtain a functionalized protein; providing a protein-reducing sugar tissue adhesive; blending the functionalized protein, reducing polysaccharides or derivatives, and hygroscopic salts, and then performing a Maillard chemical reaction and an ion complexation reaction under heating conditions by a one-pot cooking method to obtain a three-dimensional network structure to prepare the protein-reducing sugar tissue adhesive; preparing a tissue adhesive; and incubating the protein-reducing sugar tissue adhesive to reform dense and orderly hydrogen bonds in the network structure to obtain the tissue adhesive.
[0007] Preferably, the functionalized protein can be added to the protein chain through a physical modification method or a chemical modification method via the polyphenol unit-containing substance or the phenolic hydroxyl-containing small molecule.
[0008] Preferably, the physical modification method comprises mixing the protein with the polyphenol unit-containing substance or the phenolic hydroxyl-containing small molecule and then incubating the mixture through hydrogen bonding, hydrophobic interaction and other forces; preferably, the incubation temperature is 4 to 30°C.
[0009] Preferably, the chemical modification method comprises preparing the polyphenol unit-containing substance or the phenolic hydroxyl-containing small molecule through an esterification reaction or a condensation reaction.
[0010] Preferably, the polyphenol unit substance or the small molecule containing phenolic hydroxyl group includes at least one of dopamine, tannic acid, epigallocatechin, gallic acid and derivatives thereof.
[0011] Preferably, the protein includes at least one of collagen, gelatin, silk fibroin, bovine serum albumin, soybean protein or macromolecular polypeptide.
[0012] Preferably, the reducing polysaccharide has oxidizing properties, including polysaccharides containing oxidizing functional groups, that is, the reducing polysaccharide itself has oxidizing properties.
[0013] Preferably, the reducing polysaccharide is one or a combination of glucose, fructose, galactose, lactose, maltose, etc., but is not limited thereto.
[0014] Preferably, the reducing polysaccharide can be obtained by oxidation of a non-reducing polysaccharide.
[0015] Preferably, the non-reducing polysaccharide includes hyaluronic acid, starch, dextran, cyclodextrin, chitosan, but is not limited thereto.
[0016] Preferably, the hygroscopic salt comprises a chloride metal salt.
[0017] Preferably, the mass ratio of the polyphenolized functional protein, the reducing sugar and its derivatives, the chloride metal salt and the solvent is (10-100):(10-500):(30-1200):(100-3000).
[0018] Preferably, the metal chloride salt includes one or a combination of calcium chloride, magnesium chloride, ferric chloride, zinc chloride and lithium chloride, but is not limited thereto.
[0019] Preferably, the added amount of the metal chloride salt is 20-30% by mass. Unless otherwise specified, the added amount of the metal chloride salt in the present invention refers to the mass percentage.
[0020] Preferably, the metal chloride salt comprises a mixture of calcium chloride and lithium chloride.
[0021] Preferably, the mass ratio of calcium chloride to lithium chloride is (1:10)-1; more preferably, the mass ratio of calcium chloride to lithium chloride is 5-1.
[0022] Preferably, the solvent includes but is not limited to deionized water or 1% by mass acetic acid solution.
[0023] Preferably, in the one-pot cooking method, the heating temperature is 40-200°C.
[0024] Based on the problems existing in the prior art, the present invention adopts the above-mentioned preparation method to provide a tissue adhesive including an ion-quinone-based redox couple, thereby having stable conductive properties; based on this function, combined electrical stimulation therapy can promote neuronal differentiation and axon growth in vivo, enhance endogenous neurogenesis and promote functional recovery of rats with spinal cord injury.
[0025] Furthermore, the tissue adhesive has wet surface adhesion (shear adhesion strength ≥ 80 KPa), adjustable electrical conductivity (~1×10 -3 S / cm), shape adaptability, biocompatibility and biodegradability. Preferably, the wet surface adhesion strength is greater than 80KPa, so that it can be used in the integrated repair of nerve transection, specifically, including emergency hemostasis, incompressible nerve hemostasis and repair, sealed connection, and defect filling.
[0026] Furthermore, the tissue adhesive has adjustable mechanical properties that can match the mechanical properties and electrical conductivity of the natural spinal cord.
[0027] Based on the above technical solution, a synthetic process of polyphenol functionalized biological protein, reducing sugar and mixed metal chloride salts is proposed, and the Maillard chemical reaction and ion complexation reaction of the network are induced by a one-pot high temperature cooking process, and a strong and tough protein-reducing sugar-based natural polymer-based hydrogel tissue adhesive is quickly prepared. The hydrogel adhesive has the characteristics of rapid hemostasis and conductivity, and can be used for emergency hemostasis and incompressible nerve hemostasis and repair. First, the protein is modified or blended with polyphenol unit substances or small molecules containing phenolic hydroxyl groups to obtain a functionalized protein. Subsequently, the functionalized protein is blended with reducing sugars or derivatives and metal chloride salts, and Maillard chemical reactions and ion complexation reactions are carried out under heating conditions to quickly prepare a protein-reducing sugar tissue adhesive. Finally, the obtained adhesive is incubated in a refrigerator at 4°C overnight to re-form dense and orderly hydrogen bonds in the network to obtain the final tissue adhesive. Specifically, catecholated collagen, oxidized starch, and calcium chloride-lithium chloride mixed metal chloride salt were used as examples. The above-mentioned one-pot cooking strategy was used to quickly (~25 s) synthesize catecholated collagen, oxidized starch, and mixed ion (CaCl2 and LiCl) solutions by low-temperature heating to obtain a one-pot solution with elastic modulus (2-3 kPa) and electroactivity (~1×10 -3 S / cm) tissue adhesive. The tissue adhesive also has the characteristics of injectability, self-healing ability, faster and stronger wet surface adhesion (shear adhesion strength ≥ 80kPa), and the enhanced adhesion properties are due to the synergistic effect of chain reinforcement and physical force caused by the Maillard chemical reaction caused by high-temperature cooking. Based on the above characteristics, the tissue adhesive provided by the present invention can be effectively injected into the site of nerve injury and achieve incompressible nerve hemostasis and seamless filling and connection of the lesion cavity. At the same time, combined with the high mobility Li + -The formation of quinone redox couple can continuously and stably transmit electrical signals.
[0028] Furthermore, through the verification of combined electrical stimulation therapy, it is known that the injectable, functional, conductive tissue adhesive provided by the present invention can effectively regulate the local microenvironment of spinal cord injury, reduce fibrotic scar formation, promote neurogenesis, promote myelin regeneration and enhance axon regeneration, so that it can be used in the field of regenerative medicine. In particular, the present invention proposes that the multifunctional tissue adhesive can achieve hemostasis, non-destructive connection and filling of defect lesions of spinal cord injury in an integrated manner, and promote spinal cord injury regeneration, thereby providing a new integrated repair concept.
[0029] In summary, the strong and functional hydrogel adhesive synthesized by the one-pot cooking strategy of the present invention has good hemostatic and sealing effects and is a promising medical tissue adhesive for rapid hemostasis, wound sealing and injury repair.
[0030] Beneficial technical effects obtained by the present invention:
[0031] 1. The tissue adhesive provided by the technical solution of the present invention has excellent adhesive properties by the synergistic effect of chain reinforcement and physical force caused by the one-pot cooking method of the Maillard chemical reaction, so that it can have a modulus (~2kPa) and electrical activity (~1×10 -3 S / cm); it also has the characteristics of injectability, self-healing ability, faster and stronger wet surface adhesion (shear adhesion strength ≥ 80KPa), and can be effectively injected into the site of nerve injury and achieve incompressible nerve hemostasis and seamless filling and connection of the lesion cavity.
[0032] 2. The tissue adhesive provided by the technical solution of the present invention includes Li with high mobility + -quinone-based redox couple can enable tissue adhesive to ensure continuous and stable electrical signal transmission. Combined electrical stimulation therapy using injectable functional conductive tissue adhesive can effectively regulate the local microenvironment of spinal cord injury, promote neuronal differentiation and axon growth in vivo, enhance endogenous neurogenesis and promote functional recovery of rats with spinal cord injury, thereby reducing fibrotic scar formation, promoting neurogenesis, promoting myelin regeneration and enhancing axon regeneration.
[0033] 3. The tissue adhesive provided by the technical solution of the present invention is a multifunctional tissue adhesive, which further proposes an integrated repair concept, including the ability to achieve integrated hemostasis, lossless connection and filling of defect lesions for spinal cord injury, and promote spinal cord injury regeneration and other repair functions.
[0034] 4. The tissue adhesive provided by the technical solution of the present invention is a strong, multifunctional hydrogel tissue adhesive synthesized using a one-pot cooking strategy, which has good hemostatic and sealing effects and is a medical tissue adhesive for rapid hemostasis, wound sealing and injury repair with broad application prospects.
[0035] 5. The tissue adhesive provided by the technical solution of the present invention has wet surface adhesion, and the wet surface adhesion strength can reach more than 80KPa. It can seamlessly connect a completely broken spinal cord, and has shape adaptability, biocompatibility and biodegradability; it has adjustable mechanical properties and can match the mechanical properties and conductivity of the natural spinal cord.
[0036] 6. The tissue adhesive provided by the technical solution of the present invention contains hygroscopic salts and intrinsic hemostatic properties, which can quickly absorb interfacial water and hemostatic properties, thereby achieving rapid incompressible nerve hemostasis. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 It is a schematic diagram of a reaction simulation of synthesizing a protein-reducing sugar tissue adhesive by a one-pot cooking method adopted by the present invention;
[0039] Figure 2 The gelling time is monitored by a rheometer when different salt ion contents are added when preparing catecholized collagen-oxidized starch tissue adhesive in Example 1, Example 5, and Comparative Examples 1-2 of the present invention;
[0040] Figure 3 It is a statistical graph of gelation time when different salt ion contents are added when preparing catecholized collagen-oxidized starch tissue adhesive in Example 1, Example 5 and Comparative Examples 1-2 of the present invention;
[0041] Figure 4 The modulus statistics of the materials obtained when different salt ion contents were added when preparing catecholized collagen-oxidized starch tissue adhesive in Example 1, Example 5, and Comparative Examples 1-2 of the present invention;
[0042] Figure 5 This is a SEM microscopic morphology of the catecholized collagen-oxidized starch tissue adhesive prepared in Example 1 of the present invention;
[0043] Figure 6 The circular dichroism spectral curves of the catecholized collagen-oxidized starch tissue adhesive prepared in Example 1 of the present invention before and after heating;
[0044] Figure 7 This is a statistical graph of the shear adhesion strength when different salt ion contents are added when preparing the catecholized collagen-oxidized starch tissue adhesive in Example 1 of the present invention;
[0045] Figure 8 CV curves when different salt ion contents are added when preparing catecholized collagen-oxidized starch tissue adhesive in Example 1 of the present invention;
[0046] Fig. 9 The catecholized collagen-oxidized starch tissue adhesive prepared in Example 1 of the present invention combined with electrical stimulation therapy is used for BBB evaluation of motor behavior at different recovery periods after spinal cord injury repair;
[0047] Fig.10This is the histological staining result after 8 weeks of recovery after the catecholized collagen-oxidized starch tissue adhesive prepared in Example 1 of the present invention was used in combination with electrical stimulation therapy for spinal cord injury repair. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0049] The present invention provides a tissue adhesive, which adopts a one-pot cooking method to react polyphenol functionalized biological protein, reducing sugar, and metal chloride under heating conditions to obtain a functional protein-reducing sugar tissue adhesive with a polymer network structure. After the functional protein-reducing sugar tissue adhesive is incubated at low temperature, dense and orderly hydrogen bonds are reconstructed in the network structure to obtain the tissue adhesive.
[0050] See also Figure 1 , which is a reaction simulation schematic diagram of synthesizing a protein-reducing sugar tissue adhesive by a one-pot cooking method in the present invention. As can be seen from the figure, polyphenol functionalized protein, reducing polysaccharide and hygroscopic salt are added to a reaction container for reaction, and Maillard chemical reaction and ion complexation reaction are first carried out by a one-pot cooking method under heating conditions to obtain a three-dimensional network structure to prepare a protein-reducing sugar tissue adhesive, which is then incubated to reform dense and orderly hydrogen bonds in the three-dimensional network structure of the protein-reducing sugar tissue adhesive to obtain a tissue adhesive.
[0051] The tissue adhesive obtained by adopting the above technical solution has wet surface adhesion, shape adaptability, biocompatibility and biodegradability, so that it can be used in the integrated repair of nerve transection, specifically, including emergency hemostasis, incompressible nerve hemostasis and repair, sealed connection, and defect filling.
[0052] Furthermore, the tissue adhesive obtained by adopting the above technical solution has conductivity, so that it can promote neuronal differentiation and axon growth in vivo when combined with electrical stimulation therapy, enhance endogenous neurogenesis and promote functional recovery of rats with spinal cord injury.
[0053] In particular, the tissue adhesive prepared by the present invention is a one-pot cooking method with simple heating. It can be quickly prepared within a few minutes (as fast as 25 seconds), has adjustable mechanical properties and adhesion properties, and also has rapid hemostatic properties. It also has the characteristics of forming micro-batteries and thus having good conductive properties, so it can be used in the fields of emergency hemostasis of injuries and regenerative medicine.
[0054] In some preferred embodiments, the present invention also provides a method for preparing the above-mentioned tissue adhesive, which includes providing a functionalized protein; modifying or blending the protein with a polyphenol unit-containing substance or a phenolic hydroxyl-containing small molecule to obtain a functionalized protein; providing a reducing polysaccharide or a derivative; blending the functionalized protein, the reducing polysaccharide or a derivative, and a metal chloride, and then performing a Maillard chemical reaction and an ion complexation reaction under heating conditions by a one-pot cooking method to obtain a three-dimensional network structure to prepare the protein-reducing sugar tissue adhesive; preparing a tissue adhesive; and incubating the protein-reducing sugar tissue adhesive to reform dense and ordered hydrogen bonds in the network structure to obtain the tissue adhesive.
[0055] In some preferred embodiments, the physical modification method comprises mixing the protein with the polyphenol unit-containing substance or the phenolic hydroxyl-containing small molecule and then incubating the mixture at a temperature of 4 to 30°C.
[0056] In some preferred embodiments, the chemical modification method comprises preparing the polyphenol unit-containing substance or the phenolic hydroxyl-containing small molecule through an esterification reaction or a condensation reaction.
[0057] In some preferred embodiments, the polyphenol unit substance or the small molecule containing phenolic hydroxyl group includes at least one of dopamine, tannic acid, epigallocatechin, gallic acid and derivatives thereof.
[0058] In some preferred embodiments, the protein includes at least one of collagen, gelatin, silk fibroin, bovine serum albumin, soybean protein or macromolecular polypeptide.
[0059] In some preferred embodiments, the oxidized polysaccharide includes sugars that are inherently oxidizable, such as glucose, fructose, galactose, lactose, maltose, etc., or a combination of several of them.
[0060] In some preferred embodiments, the reducing polysaccharide can also be obtained by oxidation of the non-reducing polysaccharide;
[0061] In some preferred embodiments, the non-oxidative polysaccharide includes but is not limited to hyaluronic acid, starch, dextran, cyclodextrin, chitosan and the like.
[0062] In some preferred embodiments, the metal chloride salt includes one or a combination of calcium chloride, magnesium chloride, ferric chloride, zinc chloride and lithium chloride.
[0063] It should be noted that, unless otherwise specified, the tissue adhesives of different formulas synthesized in the present invention refer to the materials obtained by the synthesized formulas as tissue adhesives or conductive tissue adhesives.
[0064] The technical solution of the present invention is further described in detail below through specific embodiments.
[0065] Example 1
[0066] This embodiment provides a tissue adhesive. Taking catecholated collagen, oxidized starch and calcium chloride-lithium chloride mixed metal chloride salt as an example, the above-mentioned one-pot cooking strategy is used to quickly gelate the catecholated collagen, oxidized starch and mixed ion (CaCl2 and LiCl) solution through low-temperature heating in one pot (gelation time ~25s) to prepare a nerve repair tissue adhesive to illustrate in detail the feasibility of the technical solution of the present invention.
[0067] Specifically, the preparation method comprises the following steps:
[0068] S1. Provide catecholated functional proteins;
[0069] Weigh 500 mg of collagen and dissolve it in 50 mL of 0.5% trifluoroacetic acid, stir and dissolve it at room temperature, and completely dissolve it in about 2-3 hours. Then add 0.5 g of dopamine hydrochloride to the collagen solution, stir and dissolve it under closed conditions, and adjust the pH value of the mixed solution to 5.5 by dropping 1 mol / L sodium hydroxide solution. Then weigh 0.85 g of N-hydroxysuccinimide (NHS) and dissolve it in 15 mL of deionized water, and adjust the pH value of the mixed solution to 5.5 by dropping 1 mol / L sodium hydroxide solution. Similarly, weigh 1.15 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and dissolve it in 15 mL of deionized water, and adjust the pH value of the mixed solution to 5.5 by dropping 10% trifluoroacetic acid solution.
[0070] The prepared NHS and EDC solutions were added to the mixed solution in sequence, with an interval of 15 minutes. Finally, the entire reaction system was sealed and reacted for 20 hours at room temperature. After 20 hours, the reaction solution was transferred to a dialysis bag and dialyzed in a 4 mM hydrochloric acid solution for three days. The dialysate was replaced once a day. The purified solution was frozen at -80 degrees and freeze-dried using a freeze dryer to obtain the catecholated functional protein for standby use.
[0071] S2. Preparation of oxidative reducing sugars
[0072] Weigh 6.4g of starch and dissolve it in 100mL of dry tetrahydrofuran, fully stir at room temperature, add 1.5g of p-benzaldehyde to the starch solution after about 1 hour, stir and dissolve under airtight luminophore conditions, then add 0.08g of DMPA (2,2-dihydroxymethyl propionic acid), and similarly weigh 2g of DCC (dicyclohexylcarbodiimide) and add it to the above solution. After nitrogen is introduced, the whole reaction system is placed in an airtight state, reacted at room temperature for 18h, and after 18h, the reaction solution is transferred to a beaker, respectively washed with anhydrous ether and distilled water suction filtration three times, the purified starch is spin-dried with a rotary evaporator to obtain a white powder, which is dried and sealed for storage, i.e., oxidative reducing sugar (oxidized starch), for stand-by use.
[0073] S3. Preparation of protein-reducing sugar conductive tissue adhesive:
[0074] Dissolve the catecholized collagen with deionized water and fully dissolve the catecholized collagen by ultrasonic vibration to obtain a catecholized collagen solution with a concentration of 50 mg / mL for standby use; then pour 2 mL of the catecholized collagen solution into a 10 mL beaker, weigh 400 mg of oxidized starch, 500 mg of calcium chloride and 100 mg of lithium chloride and put them into the 10 mL beaker in sequence, place the beaker on a heating table, adjust the temperature to 80°C, and start a stirrer for rapid stirring.
[0075] Then, 1 mL of 0.1 mol / L sodium bicarbonate solution was slowly added to the beaker and stirred rapidly until the starch was completely dissolved to obtain a viscous solution, and the solution was ultrasonically centrifuged to remove bubbles; finally, the above solution was frozen and placed overnight to obtain the catecholized collagen-reduced starch conductive tissue adhesive, and the gelation time was about 25 s.
[0076] The mass percentage content of calcium chloride and lithium chloride (the mass ratio of the two is always maintained at 5:1) is 20%.
[0077] The test results show that the modulus of catecholized collagen-reduced starch conductive tissue adhesive is about 2KPa, the shear adhesion strength is about 80KPa, and the conductivity is about 9.88×10 -4 It should be noted that the modulus herein refers to the elastic modulus, which is obtained by time sweep test using a rheometer (Malvern), and the moduli described in other embodiments and comparative examples are all elastic moduli.
[0078] See also Figure 5 , is the SEM microscopic morphology of the catecholized collagen-oxidized starch tissue adhesive when the content of metal chloride ions in this embodiment is 20%. It can be seen from the figure that the molecular chain network in the network is tightly and orderly connected, and the pore size is uniform, indicating that the material has an orderly cross-linked network similar to nerve fibers. At the same time, the ordered structure with the same direction consistency further enhances the strength of the material.
[0079] Furthermore, the protein-reducing sugar conductive tissue adhesive obtained in S3 was used for repairing completely transected spinal cord injury and tested. The testing steps included:
[0080] Female rats were used. After anesthetizing the rats, a 3 cm incision was made on the back of the rats with scissors. The muscles on the dorsal side of the spine were peeled off with scissors until the bilateral vertebral plates of T9-11 were exposed. The vertebral plates were pried open to expose the spinal cord. The dura mater on one side was carefully lifted with micro forceps, and the spinal cord about 2 mm long was quickly removed from T10 with micro scissors, and hemostasis was performed to construct a full transverse spinal cord injury model. The protein-reducing sugar conductive tissue adhesive combined with electrical stimulation was used to treat rats with spinal cord injury. After nearly two months of treatment, the motor function of the rats in the protein-reducing sugar conductive tissue adhesive combined with electrical stimulation treatment group recovered the best through motor function scores and histological staining.
[0081] Example 2
[0082] The catecholized collagen was prepared according to the method of Example 1, and after freeze-drying, it was sealed and stored away from light for later use.
[0083] Dissolve the catecholized collagen with deionized water and fully dissolve the catecholized collagen by ultrasonic vibration to obtain a catecholized collagen solution with a concentration of 50 mg / mL for standby use.
[0084] Then, 2 mL of catecholized collagen solution was poured into a 10 mL beaker, 600 mg of maltose, 500 mg of calcium chloride and 100 mg of lithium chloride were weighed and put into the 10 mL beaker in sequence, the beaker was placed on a heating table, the temperature was adjusted to 80° C., and a stirrer was turned on for rapid stirring.
[0085] Then, 1 mL of 0.1 mol / L sodium bicarbonate solution was slowly added to the beaker and stirred rapidly until the maltose was completely dissolved to obtain a viscous solution, and the solution was ultrasonically centrifuged to remove bubbles;
[0086] Finally, the above solution was frozen and placed overnight to obtain catecholized collagen-maltose conductive tissue adhesive. The gelation time was about 200s. It was used in various tests and demonstration experiments. The modulus of the tissue adhesive was about 1.5KPa, the shear adhesion strength was about 100KPa, and the conductivity was about 1×10 -3 S / cm.
[0087] Example 3
[0088] Weigh 4000 mg of gelatin and dissolve it in 50 mL of 0.5% trifluoroacetic acid. Stir and dissolve at room temperature. The gelatin solution will be completely dissolved in about 0.5-1 hour.
[0089] Then, 2 g of dopamine hydrochloride was added to the gelatin solution, stirred and dissolved under closed conditions, and the pH value of the mixed solution was adjusted to 5.5 by dropping 1 mol / L sodium hydroxide solution. Then, 3.4 g of N-hydroxysuccinimide (NHS) was weighed and dissolved in 15 mL of deionized water, and the pH value of the mixed solution was adjusted to 5.5 by dropping 1 mol / L sodium hydroxide solution. Similarly, 4.6 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) was weighed and dissolved in 15 mL of deionized water, and the pH value of the mixed solution was adjusted to 5.5 by dropping 10% trifluoroacetic acid solution. The prepared NHS and EDC solutions were added to the mixed solution in sequence, with an interval of 15 minutes between each addition. Finally, the entire reaction system was sealed and reacted at room temperature for 20 hours. After 20 hours, the reaction solution was transferred to a dialysis bag and dialyzed in a 4 mM hydrochloric acid solution for three days. The dialysate was replaced once a day. The purified solution was frozen at -80 degrees and freeze-dried using a freeze dryer to obtain a functionalized protein (catecholated gelatin) for standby use.
[0090] Dissolve the catecholized gelatin with deionized water and fully dissolve the catecholized gelatin by ultrasonic vibration to obtain a catecholized gelatin solution with a concentration of 80 mg / mL for standby use.
[0091] Then, pour 2 mL of catecholized gelatin solution into a 10 mL beaker, weigh 500 mg of fructose, 500 mg of calcium chloride and 100 mg of lithium chloride and put them into the 10 mL beaker in sequence, place the beaker on a heating table, adjust the temperature to 80°C, and start a stirrer for rapid stirring.
[0092] Then, 1 mL of 0.1 mol / L sodium bicarbonate solution was slowly added to the beaker and stirred rapidly until the fructose was completely dissolved to obtain a viscous solution, and the solution was ultrasonically centrifuged to remove bubbles; finally, the above solution was frozen and placed overnight to obtain catecholized gelatin-fructose conductive tissue adhesive, and the gelation time was about 160 s.
[0093] The modulus of the tissue adhesive used in various tests and demonstration experiments was about 2KPa, the shear adhesion strength was about 100KPa, and the conductivity was about 1×10 -3 S / cm.
[0094] Example 4
[0095] Oxidized starch was prepared according to the method of Example 1, washed, dried, sealed and stored away from light for later use.
[0096] Dissolve the silk fibroin with deionized water and fully dissolve the silk fibroin by ultrasonic vibration to obtain a silk fibroin solution with a concentration of 100 mg / mL for standby use.
[0097] Then, 2 mL of silk fibroin solution was poured into a 10 mL beaker, and 1 mL of 0.1 g / mL tannic acid (TA) solution was poured into the silk fibroin stock solution. 400 mg of formaldehyde-oxidized starch, 500 mg of calcium chloride and 100 mg of lithium chloride were weighed and put into the 10 mL beaker in turn. The beaker was placed on a heating table, the temperature was adjusted to 80°C, and the stirring bar was turned on for rapid stirring.
[0098] Then, 1 mL of 0.1 mol / L sodium bicarbonate solution was slowly added to the beaker and stirred rapidly until the fructose was completely dissolved to obtain a viscous solution, and the solution was ultrasonically centrifuged to remove bubbles; finally, the above solution was frozen and left overnight to obtain a silk fibroin-tannin-reduced starch conductive tissue adhesive with a gelation time of about 20 seconds.
[0099] The modulus of the tissue adhesive used in various tests and demonstration experiments was about 3KPa, the shear adhesion strength was about 120KPa, and the conductivity was about 1×10 -3 S / cm.
[0100] Example 5
[0101] The preparation method of this embodiment is the same as that of Example 1, except that the content of the metal chloride salt is 30% (i.e., the total content of calcium chloride and lithium chloride, and the mass ratio of the two is always maintained at 5:1), and the other steps are the same as those of Example 1.
[0102] The test shows that the shear adhesion strength is about 100KPa and the conductivity is about 1×10 -3 S / cm.
[0103] Comparative Example 1
[0104] The preparation method is the same as that in Example 1, except that the content of the metal chloride salt is reduced from 20% to 10% (i.e., the total content of calcium chloride and lithium chloride, and the mass ratio of the two is always maintained at 5:1), and the other steps are the same as those in Example 1.
[0105] The protein-reducing sugar conductive tissue adhesive prepared in this comparative example has a gelation time of about 50s, a modulus of about 0.5-1KPa, a shear adhesion strength of about 50KPa, and a conductivity of about 5×10 -4 The results show that when the ion content is reduced from 20% to 10%, the adhesion strength, modulus and conductivity are significantly reduced, the adhesion strength and modulus are reduced by about half, and the conductivity is reduced by one order of magnitude.
[0106] Comparative Example 2
[0107] The preparation method is the same as that in Example 1, except that no metal chloride salt is added, that is, the content of the metal chloride salt is 0%, and the other steps are the same as those in Example 1.
[0108] The adhesion strength of the hydrogel adhesive prepared in this comparative example is significantly reduced, the shear adhesion strength is 20KPa, and the conductivity is less than 1×10 -6 S / cm, almost no conductivity.
[0109] Comparative Example 3
[0110] The preparation method is the same as that of Example 1, except that unmodified collagen is used instead of catecholized collagen.
[0111] The comprehensive properties of the hydrogel tissue adhesive prepared in this comparative example were significantly reduced, with a gelation time of about 40s, a modulus of about 1.6KPa, a shear adhesion strength of about 40KPa, and a conductivity of about 8×10 -4 S / cm.
[0112] Comparative Example 4
[0113] The preparation method is the same as that of Example 1, except that non-reducing starch is used instead of reducing starch.
[0114] The hydrogel tissue adhesive prepared in this comparative example has a gelation time of about 25s, a modulus of about 2KPa, a shear adhesion strength drop of about 45KPa, and a conductivity of about 1×10 -3 S / cm.
[0115] See also Figure 2 In the process of preparing tissue adhesives according to the methods described in Example 1 (col / C-S 20% group), Example 5 (col / CS 30% group), Comparative Example 1 (col group), and Comparative Example 2 (col / CS 10% group), when different chloride metal salt ion contents (20%, 30%, 0%, and 10%, respectively, the same below) were added, the hydrogel gelation time was accelerated with the increase of ion content. This result shows that salt ions participate in the construction of the hydrogel network, Ca 2+ It will react with the carboxyl groups on collagen. + It will interact ionically with the quinone groups on collagen to form lithium bonds, thereby forming a cross-linked network.
[0116] See also Figure 3, which is a comparison chart of the gelation time of Example 1 (col / C-S 20% group), Example 5 (col / CS 30% group), Comparative Example 1 (col group), and Comparative Example 2 (col / CS 10% group) when different contents of chloride metal salt particles were added during the preparation of tissue adhesives. It can be seen from the figure that when the mass percentage content of chloride metal salt ions is 20-30%, gelation occurs within 10 seconds, and when the salt ion content is too low or not added, the gelation time is significantly extended to more than 50s.
[0117] See also Figure 4 In the process of preparing tissue adhesives according to the methods described in Example 1 (col / C-S 20% group), Example 5 (col / CS 30% group), Comparative Example 1 (col group), and Comparative Example 2 (col / CS 10% group), when different chloride metal salt ion contents were added respectively, the modulus of the hydrogel after gelation changed significantly. As the content of chloride metal salt increased, the modulus also increased. The main reason is as mentioned above that salt ions participate in the construction of the hydrogel network. As the salt ion content increases, the complexation in the hydrogel and the ionic bond content increase significantly, thereby enhancing the strength of the hydrogel and increasing the modulus.
[0118] See also Figure 6 The circular dichroism curves of the tissue adhesive prepared according to the method described in Example 1 before and after heating prove that the secondary structure of collagen is relatively intact before and after heating. The activity of collagen affects the strength of the interaction between the hydrogel and cells, thereby affecting the adhesion of cells. The heating process often affects the activity of collagen. Therefore, we use circular dichroism tests to prove that the activity of collagen does not change significantly before and after heating. This result proves that the three-dimensional structure of collagen remains intact before and after heating, thereby keeping the biological activity stable.
[0119] See also Figure 7 When different contents of metal chloride ions were added to the tissue adhesives prepared according to the methods described in Example 1 (col / C-S 20% group), Example 5 (col / CS 30% group), Comparative Example 1 (col group), and Comparative Example 2 (col / CS 10% group) during the preparation process, the hydrogel adhesion strength increased with the increase of the ion content. This result is because the introduction of a large number of ions firstly makes the matrix more evenly dispersed, and secondly, more reversible ion interactions are formed in the network, which enhances the connection with the interface. At the same time, the enhancement of the hydrogel network jointly significantly increases the hydrogel adhesion strength.
[0120] See also Figure 8The cyclic voltammograms of the hydrogel adhesives prepared with different ion contents were measured by an electrochemical workstation for Example 1 (col / C-S 20% group), Example 5 (col / CS 30% group) and Comparative Example 2 (col / CS 10% group). The results showed that as the metal salt ion content increased, the current passing through the hydrogel also increased. This is because the increase in salt content significantly increased the ion concentration, thereby increasing the conductivity.
[0121] See also Fig. 9 , the catecholized collagen-oxidized starch tissue adhesive prepared in Example 1 was combined with electrical stimulation therapy for the motor behavior BBB evaluation of different recovery periods after spinal cord injury repair, and the control group (Control), electrical stimulation group (ES), material group (Col / CS), and electrical stimulation + material group (ES-Col / CS) were used to establish a rat spinal cord injury model. After 8 weeks of treatment with different treatment schemes, the behavior of the rats was scored. The results showed that the hydrogel prepared in Example 1 was transplanted as a tissue adhesive and combined with transcutaneous electrical stimulation to significantly enhance the motor ability of rats after spinal cord injury, which was significantly greater than the control group, the single transplantation and electrical stimulation treatment strategy group. Among them, the above-mentioned treatment scheme refers to the use of tissue engineering strategy to treat complete transverse spinal cord injury. The first group is the control group, and no treatment is performed after the injury is made; the second group is the electrical stimulation group, which refers to the transplantation of materials without electrical stimulation of the injured rats; the third group refers to the transplantation of materials to the injury site but without electrical stimulation; the fourth group refers to the transplantation of materials and electrical stimulation at the same time.
[0122] See also Fig.10 The results of histological staining after 8 weeks of recovery after the catecholized collagen-oxidized starch tissue adhesive prepared in Example 1 combined with electrical stimulation therapy for spinal cord injury repair were analyzed. The newborn spinal cord tissues of rats in different groups after 2 months of treatment were sectioned and pathologically stained. The results of H&E staining showed that the hydrogel prepared in Example 1 was transplanted as a tissue adhesive and combined with transcutaneous electrical stimulation to significantly enhance the growth of newborn spinal cord tissue, reduce the cavity area, and increase the blood vessel content. The control group, the single transplantation and electrical stimulation treatment group had significantly larger newborn spinal cord cavity areas and significantly fewer blood vessels, proving that the transplantation of hydrogel tissue adhesive combined with transcutaneous electrical stimulation can effectively promote the recovery of rats with spinal cord injury, thereby promoting the recovery of the rats' motor ability.
[0123] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0124] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a tissue adhesive, comprising: Providing functionalized proteins; chemically modifying or co-modifying proteins using polyphenol unit-containing substances or phenolic hydroxyl-containing small molecules to obtain functionalized proteins; A protein-reducing sugar tissue adhesive is provided; the functionalized protein, reducing sugar or its derivatives, and hygroscopic salt are mixed, and then a Maillard chemical reaction and an ion complexation reaction are carried out by a one-pot cooking method under heating conditions to form a three-dimensional network structure, thereby preparing the protein-reducing sugar tissue adhesive; preparing tissue adhesives; After the protein-reducing sugar tissue adhesive is incubated, dense and orderly hydrogen bonds and secondary structure are remodeled in the network structure to obtain the tissue adhesive.
2. The method for preparing the tissue adhesive according to claim 1, characterized in that: The tissue adhesive comprises an ion-quinone-based redox couple; and / or, the tissue adhesive has a shear adhesion strength of ≥80 KPa; a conductivity of about 1×10 -3 S / cm.
3. The method for preparing the tissue adhesive according to claim 1, characterized in that: The functionalized protein can be modified onto the protein chain of the protein by means of a physical or chemical modification method through the polyphenol unit-containing substance or the phenolic hydroxyl-containing small molecule.
4. The method for preparing the tissue adhesive according to claim 3, characterized in that: The physical modification method comprises the steps of mixing the protein with the polyphenol unit-containing substance or the phenolic hydroxyl-containing small molecule and then incubating the mixture through hydrogen bonding force and / or hydrophobic force; And / or, the chemical modification method includes preparing the polyphenol unit-containing substance or the phenolic hydroxyl-containing small molecule through an esterification reaction or a condensation reaction.
5. The method for preparing the tissue adhesive according to claim 1, characterized in that: The polyphenol unit substance or the small molecule containing phenolic hydroxyl group comprises at least one of dopamine, tannic acid, epigallocatechin, gallic acid and its derivatives; and / or, the protein comprises at least one of collagen, gelatin, silk fibroin, bovine serum albumin, soy protein or macromolecular polypeptide; The hygroscopic salt includes a metal chloride salt; And / or, the metal chloride salt includes one or a combination of calcium chloride, magnesium chloride, ferric chloride, zinc chloride and lithium chloride; And / or, in the one-pot cooking method, the heating temperature is 40 to 200° C.; And / or, in the one-pot cooking method, the reaction time is 25 to 300 seconds.
6. The method for preparing the tissue adhesive according to claim 5, characterized in that: The mass ratio of the polyphenolized functional protein, the reducing sugar and its derivatives, the chlorinated metal salt and the solvent is (10-100): (10-500): (30-1200): (100-3000); and / or, the metal chloride salt comprises a mixture of calcium chloride and lithium chloride; Preferably, the mass ratio of calcium chloride to lithium chloride is (1:10) to 1; more preferably, the mass ratio of calcium chloride to lithium chloride is 5 to 1; The solvent is deionized water or an acetic acid solution with a mass fraction of 1%.
7. The method for preparing a tissue adhesive according to claim 1, characterized in that: The reducing polysaccharide includes a sugar having oxidizing properties; Preferably, the reducing polysaccharide comprises one or a combination of glucose, fructose, galactose, lactose, maltose, etc.; Alternatively, the reducing polysaccharide may be obtained by oxidation of a non-reducing polysaccharide; Preferably, the non-reducing polysaccharide comprises hyaluronic acid, starch, dextran, cyclodextrin, chitosan.
8. A tissue adhesive prepared according to the preparation method according to any one of claims 1 to 7; the tissue adhesive has wet surface adhesion, adjustable electrical conductivity, shape adaptability, biocompatibility and biodegradability; in, The tissue adhesive has a shear adhesion strength of ≥80 KPa and a conductivity of approximately 1×10 -3 S / cm.
9. Use of the tissue adhesive as described in claim 8 in the integrated repair of nerve transection; the integrated repair of nerve transection includes emergency hemostasis, incompressible nerve hemostasis and repair, sealed connection, defect filling, and electrical conduction to promote neurogenesis and axon growth.
10. Use of the tissue adhesive as claimed in claim 8 in regenerative medicine, at least comprising the repair of a completely severed spinal cord without any seamless connection.
Citation Information
Patent Citations
Tissue adhesive as well as preparation method and application thereof
CN113209358A
Preparation method of biological tissue adhesive
CN113512133A
Aqueous composite binder composition and method for binding fibrous material by means of same
CN106459699A
Binders
CN106661418A
Bionic biological glue as well as preparation method and application thereof
CN114425103A
Cited By
Synaptic nerve prosthesis-like adhesive, preparation method and application thereof, and injection
CN122351562A
A decellularized dermis-containing biological patch for hernia repair and a preparation method thereof
CN122624754A